The impact of exercise modalities on blood glucose, blood pressure and body composition in patients with type 2 diabetes mellitus - Tensay Ambelu; Getu Teferi (BMC, 2023)
Abstract Background Physical activity has been recommended as an important non-pharmacological therapeutic strategy for the management of type 2 diabetes mellitus (T2DM). The aim of this study was to investigate the effects of 12 weeks of strength, aerobic, and a combination of aerobic and resistance training on blood glucose level, blood pressure, and body composition in patients with T2DM. Methods From Debremarkos referral hospital, 40 subjects with T2DM (mean age 42.45 years, 29 men, 11 women) were randomly assigned to one of three intervention groups or the control group. The following variables were measured: body mass index (BMI), fasting blood glucose (FBG), systolic blood pressure (SBP), diastolic blood pressure (DBP), and body fat percentage (BFP). Paired sample T-test and one-way ANCOVA were applied whilst controlling for diet, gender, and age. Results All intervention groups showed improvement in a mean difference of FBG − 13.03 (t =-5.55, df = 39, p < 0.001), SBP − 21.63 mmHg − 17.6 mmHg (t =-6.51, df = 39, p < 0.001), DBP − 11.86 mmHg (t = -5.47, df = 39, p < 0.001) and BFP − 9.14 (t = -7.49, df = 39, p < 0.001). There was a significant difference in mean BMI reduction when diet, gender, and age were controlled in a one-way ANCOVA (F (3, 33) = 11.79, p < 0.001), SBP (F (3, 33) = 13.383, p < 0.001), DBP (F (3, 33) = 7.830, p < 0.001), FBG (F (3, 33) = 6.337, p < 0.001), BFP (F (3, 33) = 24.29, p < 0.001) between the exercise intervention groups and control group. Additionally, the estimated marginal means indicate that the combined strength and aerobic exercise intervention group experienced the greatest improvements. Conclusion Body composition, blood pressure, and fasting blood glucose were significantly lower in the combined (aerobic plus strength) treatment than in the individual treatment, indicating that the combined exercise intervention was more successful in altering these parameters.